2017
DOI: 10.3390/nu9030238
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Dietary Quality and Dietary Guideline Adherence with Mental Health Outcomes in Adults: A Cross-Sectional Analysis

Abstract: The prevalence of adverse mental health outcomes in adults is increasing. Although beneficial effects of selected micronutrients and foods on mental health have been reported, they do not reflect the impact of the habitual diet on mental health. Therefore, our objective is to examine potential associations between dietary quality, dietary composition and compliance with food pyramid recommendations with depressive symptoms, anxiety and well-being (assessed using CES-D, HADS-A and WHO-5 screening tools) in a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 51 publications
7
47
0
Order By: Relevance
“…A meta-analysis study revealed that consumption of FV is inversely related to the risk of depression [ 10 ]. Contrary to these results, some cross-sectional studies did not find any relationship between FV consumption and depression [ 11 13 ]. Further, in a prospective cohort study, it was found that only vegetables proved to be protective against symptoms of depression, while this effect was not found for fruits [ 14 ].…”
Section: Introductionmentioning
confidence: 57%
“…A meta-analysis study revealed that consumption of FV is inversely related to the risk of depression [ 10 ]. Contrary to these results, some cross-sectional studies did not find any relationship between FV consumption and depression [ 11 13 ]. Further, in a prospective cohort study, it was found that only vegetables proved to be protective against symptoms of depression, while this effect was not found for fruits [ 14 ].…”
Section: Introductionmentioning
confidence: 57%
“…Recent studies [ 51 , 52 ] have reported a positive association between dietary quality and mental health problems. However, two previous systematic reviews [ 53 , 54 ] found limited and contradictory evidence to support the association between dietary patterns and mental health problems in adults.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong relationship between nutrition and mental health in adults [ 26 , 27 , 28 , 29 , 30 ] and has been found to differ between depressed and anxious individuals [ 26 , 27 , 28 ]. Further, diet intake has been found to differ between males and females with mental health disorders.…”
Section: Introductionmentioning
confidence: 99%